1977
DOI: 10.3406/bulmi.1977.7136
|View full text |Cite
|
Sign up to set email alerts
|

Le gîte d'axinite de Santa Rosa (municipe de Condeúba, État de Bahia, Brésil)

Abstract: Ce travail porte sur la description d'un gisement d'axinite localisé dans le sud de l'État de Bahia (Brésil), formé de veines de calcite recoupant une amphibolite en voie de serpentinisation ; le tout étant situé dans une zone broyée, encaissée dans des quartzites du Précambrien inférieur à moyen. En dehors de l'axinite, la paragenèse des veines comprend, dans un ciment de calcite : hornblende, amiante, épidote, antigorite, quartz et hyalite. Les cristaux d'axinite ont une morphologie simple et l'étude diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…All specimens exhibited typical tourmaline inclusions, such as two-phase liquid-gas inclusions, healed fractures, "feathers," and crystals (e.g., mica, figure 11). Fritsch et al (1990), Koivula et al (1992), Cassedanne (1996), and Shigley et al (2001) reported that similar features were common in "Paraíba" tourmalines from Brazil.…”
Section: Resultsmentioning
confidence: 75%
“…All specimens exhibited typical tourmaline inclusions, such as two-phase liquid-gas inclusions, healed fractures, "feathers," and crystals (e.g., mica, figure 11). Fritsch et al (1990), Koivula et al (1992), Cassedanne (1996), and Shigley et al (2001) reported that similar features were common in "Paraíba" tourmalines from Brazil.…”
Section: Resultsmentioning
confidence: 75%
“…O Pegmatito Ponte da Raiz (Figura 6A-B) corresponde a dois veios distintos, inferior e superior, subverticais e discordantes (Cassedanne et al, 1995). O inferior tem direção NE e mergulho forte para SE, com espessuras de 5-10 m. O Research, Society and Development, v. 12, n. 6, e18312642089, 2023 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v12i6.42089 10 superior possui direção ~NS e mergulho forte para W, com espessura de 10 m. Ambos são zonados, pouco diferenciados e mostram núcleo de quartzo circundado por pequenos corpos albíticos de substituição.…”
Section: Depósitos De áGua-marinhaunclassified
“…O inferior tem direção NE e mergulho forte para SE, com espessuras de 5-10 m. O Research, Society and Development, v. 12, n. 6, e18312642089, 2023 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v12i6.42089 10 superior possui direção ~NS e mergulho forte para W, com espessura de 10 m. Ambos são zonados, pouco diferenciados e mostram núcleo de quartzo circundado por pequenos corpos albíticos de substituição. Além de água-marinha e berilo industrial, o corpo inferior tem produzido cristais de topázio cujos pesos ultrapassaram 100 kg (Figura 6C), juntamente com monazita-(Ce), apatita, amazonita, fluorita e columbita (Cassedanne et al, 1995). Esses autores ressaltaram a existência de uma paragênese primária com minerais de bismuto, constituída por cosalita, bismutinita e bismuto nativo, além de uma paragênese secundária variada, com bismutita, piromorfita, cerussita, stolzita, arsenolita e enxofre nativo.…”
Section: Depósitos De áGua-marinhaunclassified